Spectrophotometric Determination of Phosphorus in Aqueous and Organic Phases Obtained on Pyrolysis of Naphtha - Prasad, Surendra; Kunzru, Deepak (Asian Journal of Chemistry, 2012)
A method for the digestion of organophosphorus compounds and the determination of phosphorus in aqueous and organic phases, which are obtained on pyrolysis of naphtha, has been proposed. The method is based on the formation of molybdivanadophosphate (MVP), which exists as stable and true yellow solution. Sample oxidation (digestion) is achieved using concentrated sulfuric and nitric acid for 30 min on water bath and subsequent heating on a medium flame to expel out sulfur trioxide fumes. The absorbance of the resulting solution was measured after proper dilution at 450 nm. The recovery and accuracy of the present method were verified by spiking experiments. Influence of foreign substances was checked. The method was applied for the determination of phosphorus in aqueous and organic phases obtained on pyrolysis of naphtha as waste product. The collective recovery of phosphorus achieved from the two (organic and aqueous phases) samples is 86%, which was quite satisfactory, while the rest 14% of phosphorus is expected go out with major gaseous products during naphtha pyrolysis. The phosphorus released with the coke was almost negligible.